Mining the gaps:using machine learning to map a million data points from agricultural research from the global south - Porciello, J.; Lipper, L.; Bourne, T.; Ivanina, M.; Lin, S.; Langleben, S. (CGIAR Research Program on Water, Land and Ecosystems, 2021)
We’re entering a new era in agriculture, one that moves beyond a purely production-oriented vision and recognizes its role in contributing to a food system that prioritizes people’s livelihoods and nutrition, as well as environmental and climate outcomes.